2013
DOI: 10.1007/978-94-007-5702-8_13
|View full text |Cite
|
Sign up to set email alerts
|

Searching for Happiness: The Importance of Social Capital

Abstract: After four decades of research, scholars of happiness continue to debate its causes. While it is generally agreed that a combination of internal and external factors play a role, predicting happiness well remains a challenge. Recent research has proposed that social capital may be a vital factor that has been overlooked. This paper attempts to address that omission. According to Coleman's (Am J Sociol 94:S95-S120, 1988) seminal work, three dimensions of social capital exist: (1) trust and obligations, (2) info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 34 publications
5
48
0
1
Order By: Relevance
“…Regarding the first hypothesis, our multi-level regression models confirmed that perceived happiness was positively and highly significantly associated with social capital at both the individual and area levels when they were used separately. These results were consistent with observations in previous studies and a well-established view of a positive association between social capital and perceived happiness (Bjørnskov 2003;Helliwell and Barrington-Leigh 2011;Leung et al 2010;Putnam 2000; Rodríguez-Pose and von Berlepsch 2014). It has been argued that social capital has a positive influence on perceived happiness through many different channels and in various forms.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Regarding the first hypothesis, our multi-level regression models confirmed that perceived happiness was positively and highly significantly associated with social capital at both the individual and area levels when they were used separately. These results were consistent with observations in previous studies and a well-established view of a positive association between social capital and perceived happiness (Bjørnskov 2003;Helliwell and Barrington-Leigh 2011;Leung et al 2010;Putnam 2000; Rodríguez-Pose and von Berlepsch 2014). It has been argued that social capital has a positive influence on perceived happiness through many different channels and in various forms.…”
Section: Discussionsupporting
confidence: 94%
“…A growing number of studies have addressed the association between social capital and perceived happiness, and a well-established view is that social capital has a favorable effect on perceived happiness (Bjørnskov 2003;Helliwell and Barrington-Leigh 2011;Leung et al 2010;Putnam 2000;Rodríguez-Pose and von Berlepsch 2014). In the current study, we have distinguished between individual-level and area-level social capital, using data from a nationwide Internet survey conducted in Japan to compare their associations with perceived happiness.…”
Section: Introductionmentioning
confidence: 99%
“…Here we directly use non-pricetagged non-material (celestial) elements which have nothing to do with market mechanisms or the economy and which may be easily regarded as 'storing up treasures in heaven'. Warm family atmospheres (Myers, 1999;Wilson and Oswald, 2002), a high level of social capital (Leung et al, 2011;Sarracino, in press), true friendship (Bruni and Stanca, 2008), the enjoyment of natural beauty (Wilson, 1984;Mayer and Frantz, 2004) or having the benefits of a clear world-view (Ellison, 1991;Clark and Lelkes, 2009) may all have this characteristic, as does benefitting from unpaid child care or receiving an English lesson in kind, too. 19 This way of gaining happiness increases celestial footprint through increasing the Easterlin factor (see central part of Table 2).…”
Section: Channels Of Gaining Happinessmentioning
confidence: 95%
“…Previous empirical studies on the effect of social capital on subjective well-being have validated that various components of social capital are positively linked to subjective well-being at both the individual and the aggregate level across countries (Helliwell & Putnam, 2004;Leung, Kier, Fung, Fung, & Sproule, 2011;Portela, Neira, & Salina-Jimen ez, 2013). There is no logical reason to assume that social capital, in general, has no impact on life satisfaction in Asian countries, as it does in Western countries.…”
Section: Previous Studies Linking Social Capital To Life Satisfactionmentioning
confidence: 99%